1993
DOI: 10.1051/gse:19930103
|View full text |Cite
|
Sign up to set email alerts
|

Marginal inferences about variance components in a mixed linear model using Gibbs sampling

Abstract: Summary -Arguing from a Bayesian viewpoint, Gianola and Foulley (1990)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
100
0
6

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(107 citation statements)
references
References 6 publications
1
100
0
6
Order By: Relevance
“…Also, for reasons of clarity and focus, I omit the description of TIM (e.g. Wang et al, 1993;Sorensen, 1996) in this section, although I do consider combinations of the FPM and TIM in the analysis of simulated data.…”
Section: Methodsmentioning
confidence: 99%
“…Also, for reasons of clarity and focus, I omit the description of TIM (e.g. Wang et al, 1993;Sorensen, 1996) in this section, although I do consider combinations of the FPM and TIM in the analysis of simulated data.…”
Section: Methodsmentioning
confidence: 99%
“…For threshold models and binary traits it has been shown that poor results can also be obtained when the posterior is close to an improper density [18]. Furthermore, impropriety of posteriors may not be easy to determine, implying the risk of obtaining misleading results [4,7,18,27].…”
Section: Introductionmentioning
confidence: 99%
“…But there can be no actual distribution to which the Gibbs picture corresponds. This was the problem with the Gibbsbased conclusions of Wang et al (1993Wang et al ( , 1994 and as they used models for which a posterior distribution did not exist.…”
Section: IImentioning
confidence: 99%
“…The sole purpose of these initial iterations was to provide the chain with ample opportunity to misbehave and alert us that something may be wrong; it never did. We chose 15,000 because a typical burn-in would probably be in the hundreds (see Wang et al 1993) so that if our chain did not misbehave during the burn-in stage, neither would that of an unknowing experimenter.…”
Section: IImentioning
confidence: 99%